Сочинения: в двух томах (Дени Дидро;[составление, редакция В. Н. Кузнецова ]) - Дидро Дени (1991)
Экземпляры: РБ (20201214☮) / Инвентарный номер: 13618 / Цена: 02.80 / Сис.шифр: 87.3(4Фра) / Авт.знак: Д44 / ББК: 87.3(4Фра)